A longitudinal assessment of depression and anxiety in the Republic of Ireland before and during the COVID-19 pandemic. (June 2021) - Hyland, Philip; Shevlin, Mark; Murphy, Jamie; McBride, Orla; Fox, Robert; Bondjers, Kristina; Karatzias, Thanos; Bentall, Richard P.; Martinez, Anton; Vallières, Frédérique
Highlights: More people suffered from major depression in February 2019 than in March-April 2020. There was no change in the prevalence of generalized anxiety disorder from February 2019 to March-April 2020. There was no change in the prevalence of major depression and GAD during six weeks of lockdown. Depression was predicted by age, non-city dwelling, loneliness, resilience, and somatic problems. GAD was predicted by sex, COVID-19 infection status, working with the public, death anxiety, internal locus of control, conscientiousness, loneliness, and somatic problems. Abstract: Few studies have examined changes in mental health before and after the outbreak of COVID-19. We examined changes in the prevalence of major depression and generalized anxiety disorder (GAD) between February 2019 and March-April 2020; if there were changes in major depression and GAD during six weeks of nationwide lockdown; and we identified factors that predicted major depression and GAD across the six-week lockdown period. Nationally representative samples of Irish adults were gathered using identical methods in February 2019 ( N = 1020) and March-April 2020 ( N = 1041). The latter was reassessed six weeks later. Significantly more people screened positive for depression in February 2019 (29.8% 95% CI = 27.0, 32.6) than in March-April 2020 (22.8% 95% CI = 20.2, 25.3), and there was no change in GAD. There were no significant changes in depression and GAD during the lockdown. Major depression was predicted by younger age, non-city dwelling, lower resilience, higher loneliness, and higher somatic problems. GAD was predicted by a broader set of variables including several COVID-19 specific variables. These findings indicate that the prevalence of major depression and GAD did not increase as a result of, or during the early phase of the COVID-19 pandemic in Ireland.